(untitled) - Bryla, Bob (Indianapolis, Ind., 2006)
Complete coverage of the exam objectives, hands-on exercises, review questions, and more, this is the first and only book to offer such in-depth coverage of this challenging exam Takes into consideration that candidates must not only know how to install and configure Oracle Application Server 10g, but how to use the robust tool set, including Oracle HTTP Server and OracleAS Portal The book features an interactive CD-ROM, including the Sybex Test Engine with chapter review questions and bonus exams, a series of flash cards that can be used on a PC or handheld, and an e-version of the book Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.
Keywords: Electronic data processing personnel,Database management,Nhân viên xử lý dữ liệu điện tử,Quản trị cơ sở dữ liệu; Certification,Examinations,Giấy chứng nhận,Kiểm tra